Hyporesponsiveness to social and nonsocial sensory stimuli in children with autism, children with developmental delays, and typically developing children. (30th April 2013) - Baranek, Grace T.; Watson, Linda R.; Boyd, Brian A.; Poe, Michele D.; David, Fabian J.; McGuire, Lorin
Abstract: This cross-sectional study seeks to (a) describe developmental correlates of sensory hyporesponsiveness to social and nonsocial stimuli, (b) determine whether hyporesponsiveness is generalized across contexts in children with autism relative to controls, and (c) test the associations between hyporesponsiveness and social communication outcomes. Three groups of children ages 11–105 months ( N = 178; autism = 63, developmental delay = 47, typical development = 68) are given developmental and sensory measures including a behavioral orienting task (the Sensory Processing Assessment). Lab measures are significantly correlated with parental reports of sensory hyporesponsiveness. Censored regression models show that hyporesponsiveness decreased across groups with increasing mental age (MA). Group differences are significant but depend upon two-way interactions with MA and context (social and nonsocial). At a very young MA (e.g., 6 months), the autism group demonstrates more hyporesponsiveness to social and nonsocial stimuli (with larger effects for social) than developmental delay and typically developing groups, but at an older MA (e.g., 60 months) there are no significant differences. Hyporesponsiveness to social and nonsocial stimuli predicts lower levels of joint attention and language in children with autism. Generalized processes in attention disengagement and behavioral orienting may have relevance for identifying early risk factors of autism and for facilitating learning across contexts to support the development of joint attention and language.